EXPLORING BEYOND SOCIAL SERVICES ADDRESSED TO ROMANIAN CHILDREN LEFT BEHIND - Alina COSTIN (Association of Social and Educational Innovation, 2023)
The child left behind (CLB) can feel the parents' migration as abandonment (Antman, 2013; Zhou, Murphy, Tao, 2014); in this case, the national legislation (Law 272/2004 and HG 691/2015) provides an institutional mechanism that supports these children, and indirectly their families. We claim to explore the way field practice takes place by talking with social workers from public social assistance services. Three focus groups with 30 participants were organized and the group discussions revealed difficulties in the application of the law determined by cultural factors, the wrong representation of the role of PSAS[1] in the community or misinformation. Five thematic units were outlined: a) low level of registration of parents who migrate, b) poor representation of PSAS in the community, c) the effectiveness of the interventions, d) the institutional mechanism, e) the condition of the children left behind. Implications for practice were discussed.